Polynomial Time Approximation Schemes for the Constrained Minimum Spanning Tree Problem - Yen Hung Chen (Journal of Applied Mathematics)
Let G=(V,E) be an undirected graph with a weight function and a cost function on edges. The constrained minimum spanning tree problem is to find a minimum cost spanning tree T in G such that the total weight in T is at most a given bound B. In this paper, we present two polynomial time approximation schemes (PTASs) for the constrained minimum spanning tree problem.